Powerful Stress Relieving Medicinal Plants for Anger, Anxiety, Depression, and Stress During Global Pandemic - Shahrajabian, Mohamad H. (Recent Patents on Biotechnology, 2022)
Consideration and improvement for anxiety and depression are important during a global pandemic. Appropriate healthcare can be obtained by paying more attention to traditional medicinal sciences. The adverse effects of stress with various symptoms can be managed by introducing plants that boost mental health. The most relevant psychological reactions in the general population related to the global pandemic are pervasive anxiety, frustration and boredom, specific and uncontrolled fear, disabling loneliness, significant lifestyle changes, and psychiatric conditions. Ginseng, chamomile, passionflower, herbal tea, lavender, saffron, kava, rose, cardamom, Chinese date, and some chief formula like yokukansan, Dan-zhi-xiao-yao-san, so-ochim-tang-gamiband, and saikokaryukotsuboreito are notable herbal treatments for mental health problems. The most common medicinal plants that have been used in Iran for the cure of stress and anxiety are Viper’s-buglosses, Dracocephalum, valerian, chamomile, common hop, hawthorns, and lavender. Medicinal plants and herbs can be used for the treatment and alleviation of the negative effects of stress, anger, and depression during the global pandemic.
Keywords: traditional herbal medicine